POSSIBLE ROLE OF MITOCHONDRIAL GENOME MUTATIONS IN CORONARY HEART DISEASE - L. A. Egorova; M. V. Ezhov; G. M. Shiganova; A. Yu. Postnov (Klinicist, 2014)
Mitochondria are not only the major producers of adenosine triphosphate, but also an endogenous source of reactive oxygen species. Mitochondrialdysfunction plays a key role in the trigger and progression of atherosclerotic lesion. Impaired function in the mitochondria due to their elevated level of oxidized oxygen species, the accumulation of mitochondrial DNA damages, and the exhaustion of respiratory chains induces dysfunction and apoptosis in the endothelial cells; activation of matrix metalloproteinases; growth of vascular smooth muscle cells and their migration into the intima; expression of adhesion molecules, and oxidation of low-density lipoproteins. Mitochondrial dysfunction may be an important unifying mechanism that accounts for the atherogenic effect of major cardiovascular risk factors. Small clinical pilot studies have shown an association of different mitochondrial genome mutations with atherosclerotic lesion in the artery. Taking into account the available data on the possible role of mitochondria in atherogenesis, novel drugs are now being designed to affect mitochondrial function.